Religious spiritual well-being: results from Muslim Iranian clinical and non-clinical samples by age, sex and group. Issue 1 (2nd January 2021) - Dadfar, Mahboubeh; Lester, David; Turan, Yahya; Beshai, James A.; Unterrainer, Human-Friedrich
ABSTRACT: The aim of the present study was to compare religious spiritual well-being between three Muslim Iranian samples: old and middle-aged adults, university students and psychiatric outpatients. The sample was a convenience sample of 561 individuals in Tehran, Iran, who completed the Multidimensional Inventory for Religious Spiritual Well-Being (MI-RSWB 48). The psychiatric outpatients had lower General Religiosity (GR), Hope Transcendent (HT), Transcendent component and total scores than the community residents, but higher Forgiveness (FO) scores. For the non-clinical females, the community residents had lower Hope Immanent (HI), GR, Connectedness (CO), Immanent component, Transcendent component and total scores and higher HT scores. We conclude that religious spiritual well-being differs between Muslim Iranian clinical and non-clinical samples, and also by age.